Clonal expansion and spread of the ceftriaxone-resistant Neisseria gonorrhoeae strain FC428, identified in Japan in 2015, and closely related isolates. (19th April 2019) - Lee, Kenichi; Nakayama, Shu-Ichi; Osawa, Kayo; Yoshida, Hiroyuki; Arakawa, Soichi; Furubayashi, Kei-Ichi; Kameoka, Hiroshi; Shimuta, Ken; Kawahata, Takuya; Unemo, Magnus; Ohnishi, Makoto
Abstract: Objectives: Ceftriaxone resistance in Neisseria gonorrhoeae is a major public health concern globally because a high-dose (1 g) injection of ceftriaxone is the only remaining option for empirical monotherapy of gonorrhoea. The ceftriaxone-resistant gonococcal strain FC428, cultured in Osaka in 2015, is suspected to have spread nationally and internationally. We describe the complete finished genomes of FC428 and two closely related isolates from Osaka in 2015, and examine the genomic epidemiology of these isolates plus three ceftriaxone-resistant gonococcal isolates from Osaka and Hyogo in 2016–17 and four ceftriaxone-resistant gonococcal isolates cultured in 2017 in Australia, Canada and Denmark. Methods: During 2015–17, we identified six ceftriaxone-resistant gonococcal isolates through our surveillance systems in Kyoto, Osaka and Hyogo. Antimicrobial susceptibility testing (six antimicrobials) was performed using Etest. Complete whole-genome sequences of the first three isolates (FC428, FC460 and FC498) from 2015 were obtained using PacBio RS II and Illumina MiSeq sequencing. The three complete genome sequences and draft genome sequences of the three additional Japanese (sequenced with Illumina MiSeq) and four international ceftriaxone-resistant isolates were compared. Results: Detailed genomic analysis suggested that the Japanese isolates (FC428, FC460, FC498, KU16054, KM383 and KU17039) and the four international MLST ST1903 isolates from Australia, Canada and Denmark formed four linked subclades. Conclusions: Using detailed genomic analysis, we describe the clonal expansion of the ceftriaxone-resistant N. gonorrhoeae strain FC428, initially identified in 2015 in Japan, and closely related isolates. FC428 and its close relatives show some genomic diversity, suggesting multiple genetic subclades are already spreading internationally.